Designer Grapes: The Socio‐Technical Construction of the Seedless Table Grapes. A Case Study of Quality Control. Issue 2 (22nd September 2017) - de Castro, Carlos; Torres‐Albero, Cristóbal
Abstract: This article focuses on agro‐food production in Murcia, Spain, and analyses the socio‐technical production processes of the seedless table grape. In the agro‐food industry, a focus on quality has driven an unstoppable process of bio‐technological innovation, which is also evident in the object of this study. Before these technological innovations, taste, colour and calibre as specific qualities of the grape were not considered a determinable characteristic. They had only emerged in the context of certain productive, technological and institutional conditions of possibility and the establishment of particular relationships between the agents implicated in its cultivation. By using Callon´s contribution to Actor Network Theory, the article examines how the different qualities of the seedless table grape are constructed through quality control procedures that try to stabilise the relationship between human (labour) and non‐human (technology, insects, fungi, water, sun) actors.